Pengaruh kepemimpinan transformasional dan kepemimpinan diri terhadap kinerja adaptif selama krisis: Peran mediasi pemberdayaan psikologi - Oktavian, Rizky Ferrari; Sriwardani; Budhi Satriawan; Ahmad Johan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to examine the effect of transformational leadership and self-leadership on adaptive performance, as well as the mediating role of psychological empowerment during the Covid-19 pandemic crisis. This research was conducted on employees of culinary SMEs in West Java by distributing questionnaires to respondents. The data was then analyzed using SEM-PLS. The findings of this study prove that transformational leadership and self-leadership have an influence on psychological empowerment, and that psychological empowerment has an influence on adaptive performance. It was also found that psychological empowerment mediates the effect of transformational leadership and self-leadership on adaptive performance. This study provides suggestions for businesses and organizations to manage and improve the adaptive performance of their employees during organizational crises.